Knowledge, attitudes and practices of antimicrobial resistance awareness among healthcare workers in India: a systematic review - Rana, Shweta; Kaur, Karuna Nidhi; Narad, Priyanka; Walia, Kamini; Saeed, Shazina; Chandra, Amrish; Shannawaz, Mohd; Singh, Harpreet (Frontiers in Public Health, 2024)
The study was conducted to identify and compile gaps in the Knowledge, Attitudes, and Practices (KAP) regarding Antimicrobial Resistance (AMR) among healthcare workers in India.A systematic review of published literature from PubMed, Google Scholar, and Scopus databases was conducted in compliance with the PRISMA guidelines. The inclusion criteria focused on studies evaluating KAP towards AMR among various healthcare workers in India without restricting context to specific diseases. We included articles published from inception to December 2023.Results: Following the inclusion criterion, 19 studies were selected for the review. The study has a cumulative sample size of 4544 healthcare providers across India. We found that doctors and medical students have significant knowledge about AMR, followed by nurses and pharmacists. However, the attitudes towards AMR were higher among informal providers, followed by doctors and medical students. The study also observed a gap between theoretical knowledge and practical application of AMR principles among healthcare providers in India.The study highlights the need for targeted training and policy interventions to bridge the gap between KAP regarding AMR. Healthcare providers can significantly contribute to mitigating AMR threat by improving KAP related to AMR. This systematic review provides a foundation for developing and implementing effective evidence-based strategies to enhance AMR containment in India.